A non-toxigenic but morphologically and phylogenetically distinct new species ofPseudo-nitzschia,P. sabitsp. nov. (Bacillariophyceae) - Teng, S.T.; Lim, P.T.; Lim, H.C.; Rivera-Vilarelle, M.; Quijano-Scheggia, S.; Takata, Y.; Quilliam, M.A.; Wolf, M.; Bates, S.S.; Leaw, C.P. (Wiley, 2015)
A new species of Pseudo-nitzschia (Bacillariophyceae) is described from plankton samples collected from Port Dickson (Malacca Strait, Malaysia) and Manzanillo Bay (Colima, Mexico). The species possesses a distinctive falcate cell valve, from which they form sickle-like colonies in both environmental samples and cultured strains. Detailed observation of frustules under TEM revealed ultrastructure that closely resembles P. decipiens, yet the new species differs by the valve shape and greater ranges of striae and poroid densities. The species is readily distinguished from the curve-shaped P. subcurvata by the presence of a central interspace. The morphological distinction is further supported by phylogenetic discrimination. We sequenced and analyzed the nuclear ribosomal RNA genes in the LSU and the second internal transcribed spacer, including its secondary structure, to infer the phylogenetic relationship of the new species with its closest relatives. The results revealed a distinct lineage of the new species, forming a sister cluster with its related species, P. decipiens and P. galaxiae, but not with P. subcurvata. We examined the domoic acid (DA) production of five cultured strains from Malaysia by Liquid chromatography-mass spectrometry (LC-MS), but they showed no detectable DA. Here, we present the taxonomic description of the vegetative cells, document the sexual reproduction, and detail the molecular phylogenetics of Pseudo-nitzschia sabit sp. nov.